Remarks on Binding Theory - Pollard, Carl (Proceedings of the 12th International Conference on Head-Driven Phrase Structure Grammar, 2005)
We propose some reformulations of binding principle A that build on recent work by Pollard and Xue, and by Runner et al. We then turn to thethorny issue of the status of indices, in connection with the seeminglysimpler Principle B. We conclude that the notion of index is fundamentally incoherent, and suggest some possible approaches to eliminatingthem as theoretical primitives. One possibility is to let logical variablestake up the explanatory burden borne by indices, but this turns out tobe fraught with difficulties. Another approach, which involves returningto the idea that referentially dependent expressions denote identity functions (as proposed, independently, by Pollard and Sag and by Jacobson)seerms to hold more promise.